CHALLENGES IN THE LIVES OF CHILDREN WITH DEVELOPMENT DISABILITIES AND THEIR PARENTS IN THE CITY OF VUKOVAR (EU and comparative law issues and challenges series (ECLIC), 2024)
Children with development disabilities are guaranteed at the international and national full and effective participation in society on an equal basis with others. They exercise their rights in the family and community in which they live. Therefore, the family and the community, as well as public policies, are factors that affect the life and realization of the rights of children with development disabilities.The aim of the paper is to gain insight into the community support for children with development disabilities and their families as well as into the realization of the rights of children with development disabilities in the city of Vukovar from the perspective of their parents.The qualitative research was conducted with parents of children with development disabilities. The results indicate the following challenges faced by parents of children with development disabilities living in the city of Vukovar: late diagnosis, lack of public and community services and professionals, lack of understanding and support in the family and community, lack of information about the rights of children and parents, challenges in the field of education, absence of parents' right to balance professional and private life, lack of leisure time for parents and fear of parents for the future of the child.